Vegetarian : The Complete Series (Hoboken, N.J. : John Wiley & Sons, 2011)
"Vegetarian eating is a healthy alternative for today's lifestyle. Meals without meat can be tasty, satisfying and easy to make. The delectable dishes in this book can be combined or enjoyed as a hearty meal on their own. Whatever the occasion, eating healthy has never been so easy" --Cover, p. [4].
Includes index.
Keywords: Vegetarian cooking